2016
DOI: 10.1007/s11548-016-1454-8
|View full text |Cite
|
Sign up to set email alerts
|

Custom implant design for large cranial defects

Abstract: In conclusion, the results show that our CAD tool can generate patient-specific implants with high accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Combining non-invasive 3D head shape scanning with nonparametric statistical shape modelling and PLS regression, it was found that craniotomy dimensions and positions of springs on average had significant effects on head shapes achieved at the time of spring removal. While previous studies have used SSM to predict the shape of missing anatomical bony parts [ 27 , 34 ] or choose best suited bone segments to plan patient-specific mandibular reconstructions [ 28 ], to the best of our knowledge, this is the first prospective study establishing direct population-based associations between craniofacial surgical choices and long-term head shape outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining non-invasive 3D head shape scanning with nonparametric statistical shape modelling and PLS regression, it was found that craniotomy dimensions and positions of springs on average had significant effects on head shapes achieved at the time of spring removal. While previous studies have used SSM to predict the shape of missing anatomical bony parts [ 27 , 34 ] or choose best suited bone segments to plan patient-specific mandibular reconstructions [ 28 ], to the best of our knowledge, this is the first prospective study establishing direct population-based associations between craniofacial surgical choices and long-term head shape outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, computer-assisted analysis of 3D medical image data has been employed to improve the head shape description [ 9 12 ] and to aid in the diagnosis of craniosynostosis [ 13 – 19 ] as well as in the evaluation of surgical outcomes [ 20 23 ]. With the aim of facilitating cranio-maxillofacial surgery, statistical shape modelling (SSM) has been used in virtual surgery planning [ 24 28 ] as well as in the design of pre-fabricated templates [ 29 31 ], surgical guides [ 32 , 33 ] and cranial implants [ 34 , 35 ] to achieve desired patient-specific post-operative outcomes on-table. However, some craniofacial procedures rely on gradual post-operative skull remodelling instead of acute changes and thus seek to obtain desired shapes not immediately on the operative table, but months later.…”
Section: Introductionmentioning
confidence: 99%
“…The pediatric craniofacial population provides distinct challenges in the design of custom made implants mainly due to congenital deformities with varying degrees of bilateral dysmorphism [21,22], thus precluding the ability to plan reconstructions based on the healthy hemi-face [23]. Moreover, the defect can be caused by a trauma [24] or a tumor's resection [16] that requires a sequence of surgical procedures. Finally, surgical correction must allow for, and anticipate, further growth and development, often with the knowledge that dysmorphic relapse may occur [25].…”
Section: Background and Aims Of The Workmentioning
confidence: 99%
“…Moreover, since every cranium is characterized by a certain degree of asymmetry, mirror imaging can lead to large deviations of affected regions during alignment of the affected and unaffected side (Quinto‐Sánchez et al, 2015 ). Alternatively, deformation‐based geometric morphometrics (GM) show a high potential for the generation of patient‐specific implants, since available morphological information of the reconstructed cranium is incorporated into the final implant (Marreiros et al, 2016 ; Mitteroecker & Gunz, 2009 ; Senck et al, 2013 ). Using thin‐plate splines (TPS), a mapping function warps the landmark configuration (template) from a complete reference specimen onto a target specimen showing cranial defects (Bookstein, 1989 ).…”
Section: Introductionmentioning
confidence: 99%